Studi Kajian Kebijakan Perdagangan Internasional dan Pertumbuhan Ekonomi Negara Berkembang - Jannah, Ayu Roudhatul; Rangkuty, Dewi Mahrani; Rusiadi Rusiadi (STIKes Ibnu Sina Ajibarang, 2024)
In the last few decades, Indonesia has witnessed significant economic development, and its role in the international trade arena has increasingly emerged. Wise trade policy is considered a crucial instrument to support and guide sustainable economic growth. This research analyzes international trade and the factors that influence international trade in Indonesia. This researcher uses descriptive methods to explain the development of international trade and verification methods to determine variables that influence international trade including: Level of tariffs and trade barriers, involvement in international trade agreements, protectionist policies, foreign direct investment, etc. By understanding how international trade policies influence economic growth in Indonesia this research seeks to provide insights that can empower the country to maximize their economic growth potential and strengthen their position in the ever-changing global economy.